DRESIS: the first comprehensive landscape of drug resistance information. Issue Volume 51:Issue D1(2023) (16th October 2022) - Sun, Xiuna; Zhang, Yintao; Li, Hanyang; Zhou, Ying; Shi, Shuiyang; Chen, Zhen; He, Xin; Zhang, Hanyu; Li, Fengcheng; Yin, Jiayi; Mou, Minjie; Wang, Yunzhu; et al.
Abstract: Widespread drug resistance has become the key issue in global healthcare. Extensive efforts have been made to reveal not only diverse diseases experiencing drug resistance, but also the six distinct types of molecular mechanisms underlying this resistance. A database that describes a comprehensive list of diseases with drug resistance (not just cancers/infections) and all types of resistance mechanisms is now urgently needed. However, no such database has been available to date. In this study, a comprehensive database describing drug resistance information named 'DRESIS' was therefore developed. It was introduced to (i ) systematically provide, for the first time, all existing types of molecular mechanisms underlying drug resistance, (ii) extensively cover the widest range of diseases among all existing databases and (iii ) explicitly describe the clinically/experimentally verified resistance data for the largest number of drugs. Since drug resistance has become an ever-increasing clinical issue, DRESIS is expected to have great implications for future new drug discovery and clinical treatment optimization. It is now publicly accessible without any login requirement at: https://idrblab.org/dresis/ Graphical Abstract: